The Role of Environmental Toxins in Infertility: Insights From Cutting-Edge Research - Sundaram, Vickram Agaram; Saravanan, Bharath; Rani Durairaj, Jenila; Balamurugan, Bhavani Sowndharya; Marimuthu, Mathan Muthu Chinnakannu; Chopra, Hitesh (Scripta Medica, 2025)
Environmental toxins are increasingly recognized for their detrimental effects on human fertility. Substances such as bisphenol A, pesticides, tobacco smoke, heavy metals, microplastics and electromagnetic fields (EMF) have been linked to concerns regarding both male and female infertility. This review examines the roles of these chemicals in infertility, focusing on recent research findings. It encompasses numerous studies that investigate the impact of environmental agents and occupational exposures on fertility. Key areas of discussion include the effects of bisphenol A, pesticides and tobacco smoke, as well as the mechanisms by which nanoparticles (NPs) and heavy metals, such as lead (Pb) and cadmium (Cd), influence fertility systems. Moreover, the review analyses the impacts of microplastics and contemporary lifestyle habits on fertility rates, alongside the effects of EMF exposure from devices such as cell phones. Recent studies underscore the pervasive influence of environmental contaminants on reproductive health. Occupational exposures and modern pollutants, including microplastics and EMFs, heighten the risk of infertility. The uncertain long-term consequences of these toxins, particularly in conjunction with genetic predispositions, pose significant concerns. Environmental toxins represent a considerable threat to fertility, necessitating stronger regulatory measures and further investigation into mitigation strategies. Future research should prioritise understanding the cumulative impact of these toxins on human reproduction.